2021
DOI: 10.1111/jnc.15449
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion kurtosis imaging detects the time‐dependent progress of pathological changes in the oral rotenone mouse model of Parkinson's disease

Abstract: Clinical diagnosis of Parkinson's disease (PD) occurs typically when a substantial proportion of dopaminergic neurons in the substantia nigra (SN) already died, and the first motor symptoms appear. Therefore, tools enabling the early diagnosis of PD are essential to identify early‐stage PD patients in which neuroprotective treatments could have a significant impact. Here, we test the utility and sensitivity of the diffusion kurtosis imaging (DKI) in detecting progressive microstructural changes in several brai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 66 publications
1
14
0
Order By: Relevance
“…Interestingly, when compared to WT mice, we observed that ASYN KO mice showed a poorer performance in the rotarod test even before exposure to rotenone. In WT mice, exposure to rotenone normally leads to impair motor function and a significant decrease in the number of dopaminergic TH + neurons in rotenone-exposed mice when compared to vehicle-treated mice [11,12,16]. Whereas there seems to be a disconnection between the normal number of TH + neurons in the SNc and the reduced performance in the rotarod test, these results would be in accordance with previous observations.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Interestingly, when compared to WT mice, we observed that ASYN KO mice showed a poorer performance in the rotarod test even before exposure to rotenone. In WT mice, exposure to rotenone normally leads to impair motor function and a significant decrease in the number of dopaminergic TH + neurons in rotenone-exposed mice when compared to vehicle-treated mice [11,12,16]. Whereas there seems to be a disconnection between the normal number of TH + neurons in the SNc and the reduced performance in the rotarod test, these results would be in accordance with previous observations.…”
Section: Discussionsupporting
confidence: 90%
“…To investigate the role of ASYN in this progression, we exposed 1-yo ASYN KO mice (B6;129×1- Snca tm1Rosl /J, Jackson Laboratories) to orally administered rotenone or vehicle for 2 and 4 months (experimental timeline in Figure 1). WT (C57BL/6) mice where used as a control for the genetic background (results already published, see Figure 3 in [16]). In ASYN KO mice, the number of TH + neurons was comparable to the number of dopaminergic neurons in the SNpc of WT mice and, contrary to what was observed in WT mice, orally administered rotenone did not induce changes in the number of TH + neurons in the SN even after 4 months of rotenone exposure (see Figure 2A-F).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, the majority of oral rotenone-PD studies claimed the model as suitable [ 21 , 23 , 25 , 26 , 27 , 28 , 29 , 30 , 33 , 34 , 35 , 37 , 43 , 44 , 58 , 59 ]. Some of these studies used different solvents, such as sunflower oil 4% or 2% carboxymethylcellulose with 1.25% chloroform, which likely affects absorption [ 59 , 60 , 61 , 62 ] but not so much first-pass metabolism. According to SwissADME prediction ( , accessed on 6 September 2022), GI absorption is per se high, and rotenone is substrate and inhibitor of cytochrome P450 enzymes.…”
Section: Discussionmentioning
confidence: 99%